Short Term Development and Fate of MGE-Like Neural Progenitor Cells in Jaundiced and Non-Jaundiced Rat Brain. Issue 4 (April 2018) - Yang, Fu-Chen; Draper, Julia; Smith, Peter G.; Vivian, Jay L.; Shapiro, Steven M.; Stanford, John A.
Neonatal hyperbilirubinemia targets specific brain regions and can lead to kernicterus. One of the most debilitating symptoms of kernicterus is dystonia, which results from bilirubin toxicity to the globus pallidus (GP). Stem cell transplantation into the GP to replace lost neurons and restore basal ganglia circuits function is a potential therapeutic strategy to treat dystonia in kernicterus. In this study we transplanted human medial ganglionic eminence (MGE)-like neural progenitor cells (NPCs) that we differentiated into a primarily gamma-aminobutyric acid (GABA)ergic phenotype, into the GP of non-immunosuppressed jaundiced (jj) and non-jaundiced (Nj) rats. We assessed the survival and development of graft cells at three time-points post-transplantation. While grafted MGE-like NPCs survived and generated abundant fibers in both jj and Nj brains, NPC survival was greater in the jj brain. These results were consistent with our previous finding that excitatory spinal interneuron-like NPCs exhibited a higher survival rate in the jj brain than in the Nj brain. Our findings further support our hypothesis that slightly elevated bilirubin levels in the jj brain served as an antioxidant and immunosuppressant to protect the transplanted cells. We also identified graft fibers growing toward brain regions that receive projections from the GP, as well as host fibers extending toward the graft. These promising findings suggest that MGE-like NPCs may have the capacity to restore the circuits connecting GP and other nuclei.